Antimicrobial activities of Malaysian plant species - Chung, P.Y.; Chung, L.Y.; Ngeow, Y.F.; Goh, S.H.; Imiyabir, Z. (2004)
Antimicrobial activities against reference Gram-positive (Staphylococcus aureus, Enterococcus faecalis) and Gram-negative (Escherichia coli, Pseudomonas aeruginosa) bacteria and Candida albicans were tested on 191 plant extracts obtained from more than 30 families of plants found in the state of Sabah, Malaysia. The plant extracts were tested by a disk-diffusion technique in which antimicrobial activity was evaluated based on the ability of the plant extracts to diffuse through agar to affect the target organisms. The extracts of Callicarpa erioclona Schau. (Verbenaceae), Callicarpa farinosa Roxb. (Verbenaceae), Sphonodesma friflora Wright (Verbenaceae), and Homalium panayanum E Villar (Flacourticeae) exhibited antimicrobial properties worthy of further investigation.